2015
DOI: 10.1371/journal.pone.0136781
|View full text |Cite
|
Sign up to set email alerts
|

ANKS3 Co-Localises with ANKS6 in Mouse Renal Cilia and Is Associated with Vasopressin Signaling and Apoptosis In Vivo in Mice

Abstract: Mutations in Ankyrin repeat and sterile alpha motif domain containing 6 (ANKS6) play a causative role in renal cyst formation in the PKD/Mhm(cy/+) rat model of polycystic kidney disease and in nephronophthisis in humans. A network of protein partners of ANKS6 is emerging and their functional characterization provides important clues to understand the role of ANKS6 in renal biology and in mechanisms involved in the formation of renal cysts. Following experimental confirmation of interaction between ANKS6and ANK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…However, whereas in mammalian cells ANKS6 localization to cilia is dependent on the presence of NEK8 (Czarnecki et al 2015), we did not observe changes in the localization of MLT-2 following NEKL-2 depletion (data not shown). In addition, ANKS6/MLT-2 colocalizes with ANKS3/MLT-3 in kidney cells (Delestre et al 2015), and these proteins physically interact through their SAM domains (Leettola et al 2014). However, because MLT-2 does not contain a predicted SAM domain, this interaction may not be conserved in C. elegans, consistent with our observation that MLT-2 and MLT-3 do not extensively colocalize.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…However, whereas in mammalian cells ANKS6 localization to cilia is dependent on the presence of NEK8 (Czarnecki et al 2015), we did not observe changes in the localization of MLT-2 following NEKL-2 depletion (data not shown). In addition, ANKS6/MLT-2 colocalizes with ANKS3/MLT-3 in kidney cells (Delestre et al 2015), and these proteins physically interact through their SAM domains (Leettola et al 2014). However, because MLT-2 does not contain a predicted SAM domain, this interaction may not be conserved in C. elegans, consistent with our observation that MLT-2 and MLT-3 do not extensively colocalize.…”
Section: Discussionsupporting
confidence: 81%
“…In mammals, mutations affecting NEK8/NEKL-2, ANKS6/MLT-2, INVS/MLT-4, and ANKS3/MLT-3 have been directly linked to a class of diseases termed ciliopathies, which result from defects in the formation of primary cilia Otto et al 2008Otto et al , 2011Trapp et al 2008;Halbritter et al 2013;Hoff et al 2013;Delestre et al 2015). These include kidney disorders, such as nephronophthisis type 2 (Otto et al 2003) and juvenile cystic kidney disease (Liu et al 2002), as well as situs inversus, cardiovascular abnormalities, liver fibrosis, and defects in other organ systems Hoff et al 2013;Manning et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent findings revealed that a defectively mutated Anks3 is causing laterality defects in an autosomal recessive manner 14 . Furthermore, recent studies revealed Anks6 as a strong interaction partner of Anks3 15 . Interestingly, Anks6 mutations in humans cause NPH with similar phenotypes in animal models 16 18 .…”
Section: Introductionmentioning
confidence: 98%